Menanamkan Nilai Nilai Qur'ani dalam Membangun Karakter Santri - Muzammil Muzammil; M Tubi Heryandi; Muharofah Nur Safitri; Iro Waziroh; Hosaini Hosaini; Moch. Sirajul Arifin (Edukais : Jurnal Pemikiran Keislaman, 2022)
Pondok Pesantren al-Munir Jombang is a boarding school that holds the Tahfidz al-Qur'an program for students. This program aims to give birth to a young generation of Muslims who have expertise in a field of knowledge and are able to lead community life and intrepreneurship, based on the Qur'an. This research was conducted to determine how the impact of the Tahfidz al-Qur'an program was felt by the students at al-Munir Jombang Islamic Boarding School. The type of research that researchers do is field research with a descriptive qualitative approach that is descriptive analysis. Data collection was carried out using the method of observation, interviews, and documentation. The results of research on the impact of the Tahfidz al-Quran program carried out by the al-Munir Jombang Islamic Boarding School on the values of character education for students, they feel a change in themselves in their daily lives in ethics based on the spirit of carrying out Islamic teachings